EFEKTIVITAS DAN DAMPAK KEBIJAKAN TAX AMNESTY BAGI PEREKONOMIAN INDONESIA - Lusy Lusy; Richard Andrew; Josephine Rebeka Teresa (Jurnal Akuntansi dan Pajak, 2023)
Taxes have a very important role for a country, the main income of Indonesian state itself also comes from taxes. At the end of August 2021, taxes had donate 1.74% of all state revenues, however, tax revenues were still not optimal. To push state tax revenues, the government proposes a tax amnesty policy (Tax Amnesty). Tax Amnesty is the abolition of taxes that should be paid by disclosing assets and paying a ransom as regulated in Law no. 11 of 2016 concerning Tax Amnesty. The General Purpose of Tax Amnesty is carried out to withdraw "money" from taxpayers which is allegedly kept secret in tax-free countries. The tax amnesty policy it will give an impact with increase incoming money from taxpayers and increase government capital that can be used for the welfare of the people and balance the economy in Indonesia. The method used in this study is a literature study research method. Based on the research has been done it can be concluded that the tax amnesty policy in Indonesia still not running effectively yet, but has a positive impact on the growht of tax revenue